Mosquito Control and Beekeepers - Jamie Ellis; Jerry Hayes (EDIS)
ENY-149, a 3-page fact sheet by Jamie Ellis and Jerry Hayes, addresses the concern among beekeepers in Florida over mosquito control programs and how they may impact honey bee colonies. Published by the UF Department of Entomology and Nematology, December 2008.